Utilizing the Modern Technological Means in Facing Christianization - Mohamed Hamed Mohamed Said, Shaaban Abdelhameed Refae Mohamad ,Mohamed Shafei Moftah Bosheya (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The appearance of modern technology had a clear effect on how people communicate as well as on publishing information. As, it enabled millions of people around the world to communicate and exchange ideas and opinions. Now it is possible for anyone around the world to communicate with people far away from him geographically. In addition, it also allowed publishing huge amounts of information in various aspects of life and made obtaining it easy and affordable. In spite of that, the most important disadvantage of these means is the lack of legal accountability which allowed many users to freely publish their ideas, even if it affects the freedom and beliefs of others. Moreover, these means have helped in publishing undocumented news, as there are no restrictions on publishing through it. Non-Muslims have sought to harness these means to spread their religion and preaching it to various parts of the world and make Muslims question their religion and try to distract them away from it. At the top of these campaigns, is the Christianization campaigns that strive to divert the largest possible number of Muslims from their religion. Therefore, Muslims must pay more attention and do more efforts to repel these attacks and refute their claims. This research comes to reveal some of the attempts and efforts that are done to Christianize the Muslim (convert them to Christianity) and to divert them from their religion. The research also deals with how Muslims can utilize modern technological means in facing these efforts and revealing their falsehood, nullity and its malicious intent and warning Muslims from following them.The research also includes the definition of the concept of modern technological means and their importance. It also includes models of modern technological means and how to benefit from them in facing the Christian thought and clarify the most important characteristics which those who are responsible for facing Christianization campaigns through modern technological means, must have.